Ultrasound-Guided Supraorbital Nerve Block For Orbital Chronic Cancer Pain - A Case Report - Mochamat Mochamat (JAI (Jurnal Anestesiologi Indonesia))
Background: Many individuals with cancer suffer from pain symptom, typically ranging from moderate to severe levels. Multimodal approach has been used widely to manage the cancer pain. The ultrasound-guided peripheral nerve block has increasingly been used in the interventional pain management of chronic pain cases.